Capitalism as civilisation : a history of international law - Tzouvala, Ntina (Cambridge, United Kingdom ; New York, NY, USA : Cambridge University Press, 2020)
"This book offers the first comprehensive history of the standard of civilisation in international law. Methodologically and theoretically innovative, this monograph draws from Marxism and deconstruction bringing together the textual and the material in our understanding of law. Approaching 'civilisation' as an argumentative pattern related to the distribution of rights and duties amongst different communities, Tzouvala illustrates both its contradictory nature and its pro-capitalist bias. 'Civilisation' is shown to oscillate between two poles. On the one hand, a pervasive 'logic of improvement' anchors legal equality to demands that non-Western polities undertake extensive domestic reforms and embrace capitalist modernity. On the other, an insistent 'logic of improvement' constantly postpones and engages such a prospect based on ideas of immutable difference. By detailing the tension and synergies between these two logics, Tzouvala argues that international law incorporates and attempts to mediate the contradictions of capitalism as a global system of production and exchange that both homogenises and stratifies societies, populations and space"--
The Standard of civilisation in international law : politics, theory, method -- The standard of civilisation in the nineteenth century : between the 'logic of improvement' and the 'logic of biology' -- The institutionalisation of civilisation in the interwar period -- Arguing with borrowed concepts : 'the sacred trust of civilisation' in the South West Africa Saga -- From Iraq to Syria : legal arguments for the civilising missions of the twenty--first century -- Thinking through contradictions on a warming planet.
Based on author's thesis (doctoral - Durham University, 2016) issued under title: Letters of blood and fire : a socio-economic history of international law.
Includes bibliographical references and index.
Keywords: International law -- Moral and ethical aspects; International law -- Social aspects